Consciousness and the Preservation of the Environment: A Panpsychist Perspective - Ogonegbu, Festus Chukwunweike (Studia Ecologiae et Bioethicae, 2025)
The environmental crisis confronting humanity demands not only technological solutions but also a profound philosophical reimagining of our relationship with nature. This paper examines how panpsychism, the philosophical position that consciousness or mentality is fundamental and ubiquitous throughout the universe, offers valuable resources for environmental ethics and conservation practices. While conventional Western ontologies maintain a sharp divide between conscious humans and non-conscious nature, panpsychism suggests a fundamental continuity throughout the natural world that transforms our ethical responsibilities toward environmental preservation. Employing analytical and phenomenological approaches, this paper argues that the recognition of consciousness in natural entities provides philosophical foundations for acknowledging their intrinsic value beyond instrumental utility to humans. Furthermore, it contends that panpsychist principles, when integrated with Indigenous knowledge systems that have long recognized agency and personhood in nature, offer holistic approaches to environmental challenges that honour both philosophical coherence and practical wisdom. The paper concludes that while environmental degradation continues at unprecedented rates, a panpsychist perspective can contribute to developing more reciprocal relationships with natural systems based on mutual recognition rather than instrumental exploitation, potentially addressing both the metaphysical foundations and practical manifestations of our environmental predicament.